The Influence Of Competency, Job Satisfaction, And Organizational Commitment On Employee Performance At The Medan Madya Tax Services Office - Nuryana, Ferda; Fitriyanti, Fitriyanti; Darika, Darika; Syakarwi, Ahmad; Supriadi, Supriadi; Nasti, Nilawati (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
This examination means to decide the impact of skill, work fulfillment and authoritative responsibility to some degree and, at the same time, representative execution at the Medan Moderate Expense Administration Office. The examination was led at the Medan Halfway Expense Administration Office, Jalan Sukamulia Number 17A Medan, with a population of 122 individuals and an exploration test of 55 individuals. Information assortment was completed through meetings, polls and documentation. Using version 24 of the IMB Statistics for Product and Service Solution (SPSS) computer program, multiple regression analysis was used to analyze the data. In view of the consequences of the examination, it was found that skill significantly affected the exhibition of the Medan Moderate Duty Administration Office workers. This was upheld by the consequences of the investigation of t count > t-table (3,529 > 2,008) at n = 55 at an importance level of 95%. Work fulfillment significantly affects the exhibition of Medan Moderate Expense Administration Office representatives; this is upheld by t count > t-table examination (2,035 > 2,008) at n = 55 at an importance level of 95%. Hierarchical responsibility meaningfully affects the presentation of Medan Middle Expense Administration Office workers; this is upheld by t count > t-table examination (2,833 > 2,008) at n = 55 with an importance level of 95%. The worth of F-count > F table (22.284 > 2.79) states that together, there is a positive and huge impact of skill, work fulfillment and hierarchical responsibility on the presentation of representatives of the Medan Middle of the Road Expense Administration Office.